Some Problems of Criminal Liability for Illegal Extraction of Biological Water Resources - O. S. Pozdeeva (Сибирское юридическое обозрение)
In this article the attention is focused on the problems arising from qualification of signs of the objective party of a crime structure (Art. 256 of the Сriminal Code of the Russian Federation); the ways of further improvement of this criminal rule of law are offered as well.